2005
DOI: 10.1016/j.freeradbiomed.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized-1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine induces vascular endothelial superoxide production: Implication of NADPH oxidase

Abstract: Modified low-density lipoprotein (LDL) induces reactive oxygen species (ROS) production by vascular cells. It is unknown if specific oxidized components in these LDL particles such as oxidized-1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine (ox-PAPC) can stimulate ROS production. Bovine aortic endothelial cells (BAEC) were incubated with ox-PAPC (50 μg/ml). At 4 h, ox-PAPC significantly enhanced the rate of O 2 −• production. Pretreatment of BAEC in glucose-free Dulbecco's modified Eagle's medium plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 67 publications
3
48
1
3
Order By: Relevance
“…Such oxidized lipids are generated by the interaction of unsaturated FAs with ROS either free in solution or coordinated by enzymes including the di-iron oxidases (e.g., lipoxygenase) and heme-monoxygenases (e.g., cytochrome P450s; CYP). Various oxidized lipids, including oxidized cholesterol (52) and oxidized-1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine (53), are reported to induce cellular responses that can promote the generation of ROS. Although LDLs are prominent targets for postprandial oxidative modification in humans, the balance of factors controlling LDL oxidation in vivo remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Such oxidized lipids are generated by the interaction of unsaturated FAs with ROS either free in solution or coordinated by enzymes including the di-iron oxidases (e.g., lipoxygenase) and heme-monoxygenases (e.g., cytochrome P450s; CYP). Various oxidized lipids, including oxidized cholesterol (52) and oxidized-1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine (53), are reported to induce cellular responses that can promote the generation of ROS. Although LDLs are prominent targets for postprandial oxidative modification in humans, the balance of factors controlling LDL oxidation in vivo remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Several pieces of data reported here support the regulation of OKL38 by oxidative stress. First, OKL38 stimulation by OxPAPC requires the activity of Nox, which is a major source of cellular superoxide production in response to OxPAPC (13). Second, scavenging of superoxide by the antioxidant NAC blocks the stimulation of OKL38.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that OxPAPC induces superoxide production in endothelial cells and that superoxide induction by OxPAPC is mediated by NADPH oxidase (Nox) and uncoupled endothelial Nitric Oxide Synthase (eNOS) (13,14). In cells treated with OxPAPC, superoxide was shown to be involved in the expression of interleukin-8 in HAECs and of Matrix Metalloprotease-2 (MMP2) in bovine aortic endothelial cells (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rouhanizadeh et al demonstrated that glutathione was depleted in response to Ox-PAPC treatment in bovine aortic endothelial cells and that NADPH oxidase was the source superoxide induction by Ox-PAPC, which led to glutathione depletion. 45 Therond et al observed a decrease in glutathione levels in response to short chain polar lipid derivatives in endothelial cells. 46 Gharavi et al demonstrated that superoxide produced by uncoupled e-NOS also is a source of ROS.…”
Section: Regulation Of Oxidative Stressmentioning
confidence: 99%